Women’s Motivation in Utilizing Culture for Sustainable Economic Improvement at Desa Pesanggrahan - Wahyuni, Lilik; Utaminingsih, Alifiulahtin; Uyun, Dhia Al; Riniwati, Harsuko; Wike, Wike; Setyiawati, Eti; Almira, Nabila Sella; Arifin, Nur Hikmah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Women play a crucial role in driving advancements in the local economy in alignment with the Sustainable Development Goals. This research seeks to offer an unbiased understanding of women’s motivational levels, perspectives, and roles in Desa Pesanggrahan, Mojokerto, East Java, contributing to the development of their cultural landscape. This descriptive qualitative study utilized data collected from August to September 2023 through document reviews, interviews, and observations with female members of the Family Welfare Development (Pembinaan Kesejahteraan Keluarga [PKK]) in Desa Pesanggrahan organization in Desa Pesanggrahan. We employed Abraham Maslow's theory on the hierarchy of needs as a base for the analysis of this paper. The result of interviews with the locals, documentation, and observation carried out in the data collection of this research found that women in Desa Pesanggrahan still have low motivation based on Maslow’s theory. This affects their ability to generate innovative ideas and make independent decisions in the development of local culture. Women tend to select men as their leaders, as they often lack the confidence to assume leadership roles in the village. Their role in developing their cultural products in the village is overshadowed by the men of the village.